1988
DOI: 10.1002/jor.1100060406
|View full text |Cite
|
Sign up to set email alerts
|

Pressure distribution in the wrist joint

Abstract: We performed a study to determine pressure distribution properties of the normal radio-carpal joint. A system was developed for measurement of the contact pressure within the wrist joint surfaces. The transducer was based on Fuji pressure-sensitive paper, which was inserted into the joint space through a dorsal capsular incision. The hand was then positioned using a jig that permitted free axial loading of the joint. Each of five specimens was tested in 36 positions combining flexion/extension with radio/ulnar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 14 publications
2
28
0
2
Order By: Relevance
“…5,13,34,37 The earlier-described biomechanic study shows that rigid fixation can be achieved by fixed-angle volar plating with subchondral screw placement.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…5,13,34,37 The earlier-described biomechanic study shows that rigid fixation can be achieved by fixed-angle volar plating with subchondral screw placement.…”
Section: Discussionmentioning
confidence: 97%
“…Because we were using a distal forearm model the total load applied to the radius was about 640 N, because the ulna in this setting takes up 18% to 20% of the total load applied to the forearm. 25,[33][34][35] Based on the calculations of Putnam et al 23 an 800-N load to the forearm therefore corresponds to grip forces between 100 and 200 N. In osteoporotic bone, however, the forces necessary to cause postoperative radial shortening are probably even lower.…”
Section: Discussionmentioning
confidence: 98%
“…Tencer et al (1988) reported radiocarpal contact area ratios data for 36 different forearm and wrist positions. For neutral radioulnar deviation, they reported the radioscaphoid to radiolunate contact area ratio as 3.72 with neutral flexion-extension and 2.19 with 201 of wrist extension.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, for human joints, contact areas of 50 mm 2 (the high end of values tested here, Fig. 2) are representative of finger and wrist joints, which typically experience stresses of 0-3 MPa (Tencer et al, 1988;Ateshian et al, 1995). For the patellofemoral joint, contact areas may be as high as 400 mm 2 , with peak contact stresses of 4.5 MPa under normal activities Huberti and Hayes, 1984).…”
Section: Article In Pressmentioning
confidence: 99%